Durable rust-proof metal storage box coated with protective coating and coating method of durable rust-proof metal storage box

By forming a micron-level elliptical hole structure on the surface of the metal storage box and dispersing the coating using electrophoresis to form a layered structure, the problem of insufficient anti-rust performance of the metal storage box is solved, the adhesion and durability of the coating are improved, and the use is extended. life.

CN119194564APending Publication Date: 2024-12-27YANGZHOU HUARUI METAL PROD CO LTD

Patent Information

Application Number
CN202411719550.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing metal storage boxes are prone to oxidation and corrosion in humid environments, resulting in insufficient anti-rust performance, poor coating adhesion, easy peeling, and the existing anti-rust process is high cost or poor durability.

Method used

Laser drilling is used to form a micro-scale elliptical pore structure, and fine and coarse-grained coatings are used to uniformly disperse them on the metal surface and pore structure through electrophoresis to form a layered structure, combining electric field force and high-temperature baking to form a dense coating.

Benefits of technology

It improves the adhesion and durability of the coating, enhances the anti-rust performance, extends the service life of the metal storage box, and resists stress concentration caused by mechanical wear and thermal expansion and contraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194564A_ABST
    Figure CN119194564A_ABST
Patent Text Reader

Abstract

The invention discloses a durable rust-proof metal storage box coated with a protective coating and a coating method of the durable rust-proof metal storage box. The coating method comprises the steps that a plurality of needed metal storage boxes are selected, and oil stains and oxidation films on the surfaces of the metal storage boxes are removed through an electrolytic method; the method comprises the following steps: performing laser drilling treatment on the surface of a metal storage box to process a micron-sized elliptical hole structure, then performing high-temperature modification on the surface of the metal storage box, preparing an electrophoresis tank, adding an electrophoresis solution, and immersing the metal storage box as a cathode into the electrophoresis solution, applying a direct-current electric field to uniformly disperse the coating in the electrophoretic liquid onto the surface of the metal storage box and into the elliptical hole structure to form a layered structure; the dip-coated metal storage box is subjected to high-temperature baking and hot pressing to form a uniform protective coating; the elliptical hole structure is filled with the coatings with different particle sizes, and the coatings are distributed on the surface of the metal storage box, so that the layered structure of the coating is realized, the mechanical embedding between the coating and the metal box base body is increased, and the adhesive force of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal storage box coating, and in particular to a durable rust-proof metal storage box coated with a protective coating and a coating method thereof. Background Art

[0002] Metal storage boxes are widely used in modern industry and family life, mainly for storing and protecting various items, such as tools, parts, documents and valuables. Metal storage boxes have good strength, durability and fire resistance, so they are widely used in manufacturing, automobile repair, home storage and other fields. Especially ferrous metal storage boxes, which are mainly made of ferrous metals, namely iron, manganese, chromium and their alloys. These metal storage boxes are popular because of their high hardness, non-deformation and wear resistance. At the same time, they also have the advantages of light weight, high compressive strength, stable properties and long service life. However, they are prone to oxidation corrosion in humid environments, which shortens their service life and may damage the items stored inside. Therefore, how to improve the rust resistance of metal storage boxes is also an important research direction.

[0003] The main purpose of applying a protective coating to the surface of a metal box is to enhance the rust resistance and durability of the black metal storage box, protect it from erosion by the external environment, and thus extend its service life. Anti-rust measures for metal boxes mainly include applying anti-rust oil, using anti-rust paint, galvanizing, etc. These methods can improve the anti-rust performance of metal storage boxes to a certain extent, but there are some limitations: anti-rust oil and anti-rust paint have poor durability and are easily affected by mechanical wear and environmental factors; although the galvanizing process can provide better anti-rust effects, the process is complicated and the cost is high.

[0004] In the prior art, when coating a protective layer on a metal storage box, in addition to applying anti-rust oil, using anti-rust paint, and galvanizing, powder coating or thermal spraying is usually used to form a dense coating on the metal surface. The anti-rust performance of the metal box obtained by this method is improved, and the coating efficiency is high, but there are still certain problems. During the powder coating process, because the metal surface is too flat, when the powder coating is directly applied, the physical and mechanical locking effect between the coating and the metal surface is weak, and the adhesion is insufficient. At the same time, when the directly applied coating is subjected to external forces, especially when the metal material undergoes thermal expansion and contraction or mechanical vibration, it may cause uneven stress distribution inside the coating, which can easily cause cracking or peeling of the coating. Summary of the invention

[0005] The present invention overcomes the deficiencies of the prior art and provides a durable rust-proof metal storage box coated with a protective coating and a coating method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a coating method for a durable rust-proof metal storage box coated with a protective coating, comprising the following steps: S1. Place the required metal storage box into an electrolytic bath, and remove the oil and oxide film on the surface of the metal storage box by electrolysis; S2, performing laser drilling on the surface of the treated metal storage box to produce a number of micron-level elliptical hole structures; S3, placing the metal storage box obtained in S2 into a silane coupling agent solution and performing high-temperature modification; S4, pouring electrophoresis liquid into the electrophoresis tank, immersing the metal storage box as a cathode into the electrophoresis liquid, applying a DC electric field to evenly disperse the coating in the electrophoresis liquid onto the surface of the metal storage box and into the elliptical hole structure to form a layered structure; The coating comprises fine coating and coarse-grained coating, and the fine coating is uniformly filled into the micron-scale elliptical pore structure through an electric field, and the coarse-grained coating is uniformly dispersed and deposited on the surface of the metal storage box; wherein the fine coating is set as a composite structure, including a shell layer and an inner layer, the shell layer is selected from one of phenolic resin and polyethylene, the inner layer is selected from aluminum oxide particles with a particle size of 20-40nm and nano-silica with a particle size of 50-80nm, and the coarse-grained coating is selected from zinc powder coating with a particle size of 5-30μm and epoxy resin coating with a particle size of 10-30μm; The micron-scale elliptical hole structure has a short axis of 10-30 μm, a long axis of 30-90 μm, and a depth of 30-70 μm; S5. The metal storage box obtained in S4 is baked at high temperature and hot-pressed to form a uniform protective coating.

[0007] In a preferred embodiment of the present invention, the metal storage box in S1 is made of iron alloy, manganese alloy or chromium alloy.

[0008] In a preferred embodiment of the present invention, a nanosecond laser processing system is used for laser drilling on the surface of the metal storage box, and the parameters of the nanosecond laser processing system are set as follows: speed of 10-300 mm / s, frequency of 10-30 kHz, and power of 5-50 W.

[0009] In a preferred embodiment of the present invention, the micron-scale elliptical hole structure has a short axis of 10-30 μm, a long axis of 30-90 μm, and a depth of 30-70 μm.

[0010] In a preferred embodiment of the present invention, the silane coupling agent in S3 adopts a γ-aminopropyltriethoxysilane solution with a concentration of 1%; wherein, the high-temperature modification process is: soaking the metal storage box with clean water to produce a seamless water film, and immediately immersing it in the γ-aminopropyltriethoxysilane solution for 8-12 minutes. After the immersion is completed, take out the metal storage box for drying, and keep it at a high temperature of 100-130°C for 20-30 minutes.

[0011] In a preferred embodiment of the present invention, the coating in S4 includes fine coating and coarse-grained coating, and the fine coating is evenly filled into the elliptical hole structure through an electric field, and the coarse-grained coating is evenly dispersed and deposited on the surface of the metal storage box; wherein the fine coating is configured as a composite structure, including a shell layer and an inner layer, and the fine coating is selected from alumina particles and nano-silica, and the coarse-grained coating is selected from zinc powder coating and epoxy resin coating.

[0012] In a preferred embodiment of the present invention, the electrophoretic liquid in S4 is made of the following components in mass percentage: water 85-90%, disodium hydrogen phosphate 0.5-1%, sodium dihydrogen phosphate 0.5-1%, sodium chloride 0.1-0.5%, sodium dodecyl sulfate 0.1-0.5%, composite alumina particles 1-2%, composite nano-silica 0.5-1%, zinc powder coating 5-7%, epoxy resin coating 3-5%, polyethylene glycol 0.1-0.5%, sodium benzoate 0.05-0.1%, ethylene glycol 0.1-0.5%; The fine coating is a mixture of two coatings. The first coating is composite alumina particles, the shell of which is phenolic resin and the inner layer is alumina particles. The second coating is composite nano-silica, the shell of which is phenolic resin and the inner layer is nano-silica.

[0013] In a preferred embodiment of the present invention, in S4, a direct current electric field is applied to the electrophoresis liquid, the electric field strength is 150-250V, and the electrophoresis time is 2-10min.

[0014] A coating device for a durable rust-proof metal storage box coated with a protective coating, characterized in that it comprises: a coating platform, and an electrolytic cell, a laser drilling system, a modification treatment device and an electrophoresis tank cooperatively arranged on the coating platform; An anode and a cathode are arranged inside the electrolytic cell, the anode is made of stainless steel, and the cathode is a metal storage box to be processed; a mobile platform is installed on the coating platform, and the laser drilling system is installed on the mobile platform, and the laser drilling system includes a nanosecond laser, an optical system and a scanning head arranged in cooperation with the nanosecond laser; The modification treatment equipment includes an infiltration tank, a silane solution tank and a drying device; the electrophoresis tank is filled with electrophoresis liquid, and an electrode system and a power supply system are arranged in the electrophoresis tank, the anode in the electrode system is made of stainless steel, the cathode is a modified metal storage box, and the power supply system is used to apply a DC electric field.

[0015] In a preferred embodiment of the present invention, a baking oven and a heat press are further provided on the coating platform, the baking oven and the heat press are connected via a conveyor, and a temperature control system is provided in the baking oven and the heat press.

[0016] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention proposes a coating method for a durable and rust-proof metal storage box coated with a protective coating, wherein a micron-sized elliptical hole structure is processed on the surface of the metal storage box by laser drilling, and coatings with different particle sizes are filled into the elliptical hole structure and distributed on the surface of the metal storage box to achieve a layered structure of the coating, thereby increasing the mechanical fit between the coating and the metal box substrate, improving the adhesion of the coating, and preventing the coating from peeling off. The use of fine coating can fill the interior of the micron-sized elliptical hole structure to form a dense protective layer, effectively blocking the penetration of corrosive media and enhancing the anti-corrosion performance. The use of coarse-grained coating also forms a harder protective layer on the outer layer, which greatly resists external mechanical wear, thereby extending the service life of the metal storage box.

[0017] (2) The present invention fills the composite alumina particles with shell layers and composite nano-silica in the fine coating into the elliptical hole structure, and after baking, the fine coating with the shell layer of polyester resin material expands and combines with the zinc powder coating and epoxy resin coating deposited on the metal surface. Since the edge of the elliptical groove is sharper than that of the circular groove, the local contact area of ​​the edge is increased, thereby providing more contact points after the coating is cured, improving the mechanical interlocking between the coating and the metal surface at the edge of the elliptical hole groove, enhancing the adhesion of the coating, and further improving its durability. In addition, the major axis and minor axis of the elliptical groove show different stress concentration effects under stress, which prompts the coating material to form a tighter combination at the edge of the groove. In addition, the micron-sized elliptical hole and the layered coating structure can effectively alleviate the stress concentration caused by thermal expansion and contraction, reduce the risk of coating cracking, and further improve the adhesion of the coating.

[0018] (3) The present invention applies fine-grained paint and coarse-grained paint by electrophoresis, and utilizes electric field force to evenly disperse the paint on the metal surface and in the elliptical holes, thereby ensuring the uniformity and integrity of the coating. In addition, the fine-grained paint and coarse-grained paint are evenly distributed during the electrophoresis process, so that the coating not only has good corrosion resistance in the subsequent baking and hot pressing process, but also can effectively prevent stress corrosion cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a flow chart of the coating method of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0022] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood by specific circumstances.

[0023] like Figure 1 As shown, a coating method for a durable rust-proof metal storage box coated with a protective coating comprises the following steps: S1. Place the required metal storage box into an electrolytic bath, and remove the oil and oxide film on the surface of the metal storage box by electrolysis; S2, performing laser drilling on the surface of the treated metal storage box to produce a number of micron-level elliptical hole structures; S3, placing the metal storage box obtained in S2 into a silane coupling agent solution and performing high-temperature modification; S4, pouring electrophoresis liquid into the electrophoresis tank, immersing the metal storage box as a cathode into the electrophoresis liquid, applying a DC electric field to evenly disperse the coating in the electrophoresis liquid onto the surface of the metal storage box and into the elliptical hole structure to form a layered structure; S5. The metal storage box obtained in S4 is baked at high temperature and hot-pressed to form a uniform protective coating.

[0024] Among them, the metal storage box in S1 is made of iron alloy, manganese alloy or chromium alloy, and the specific process of the electrolysis method is to use clean water to preliminarily clean the metal storage box to remove most of the impurities and oil stains on the surface, install a stainless steel anode on one side of the electrolytic cell, fix the metal storage box to be treated on the cathode fixture, and pour the prepared electrolyte into the electrolytic cell to ensure that the liquid level immerses the electrode and the metal storage box; Connect the electrodes to the power supply, connect the stainless steel anode to the positive pole, and the metal storage box cathode to the negative pole. Turn on the power and adjust the current density to 0.1-0.5A / d㎡, and the voltage to 6-12V. Start the electrolysis reaction. The electrolysis time is 5-20min. Adjust according to the degree of contamination on the metal surface. Wait for the electrolysis to end. Use clean water to thoroughly clean the metal storage box to remove the residual electrolyte, and neutralize it. Then put the metal storage box in a drying oven and dry it at low temperature.

[0025] The raw materials used in preparing the electrolyte include 10-20% sulfuric acid, 5-15% phosphoric acid and 70-80% aqueous solvent by weight. During the preparation process, sulfuric acid is slowly added to the aqueous solvent while stirring to avoid excessive temperature. After the sulfuric acid is completely dissolved, phosphoric acid is slowly added and stirring is continued until completely mixed to obtain the electrolyte.

[0026] In step S2, a nanosecond laser processing system is used for laser drilling of the surface of the metal storage box, and the parameters of the nanosecond laser processing system are set as follows: speed is 10-300 mm / s, frequency is 10-30 kHz, and power is 5-50 W. The short axis of the micron-scale elliptical hole structure is 10-30 μm, the long axis is 30-90 μm, and the depth is 30-70 μm.

[0027] In step S3, the silane coupling agent uses a γ-aminopropyltriethoxysilane solution with a concentration of 1%; wherein, the high-temperature modification process is: soak the metal storage box with clean water to produce a seamless water film, and immediately immerse it in the γ-aminopropyltriethoxysilane solution for 8-12 minutes. After the immersion is completed, take out the metal storage box for drying, and keep it at a high temperature of 100-130°C for 20-30 minutes; wherein, the purpose of high-temperature modification of the surface of the metal storage box is to enhance the bonding force between the metal surface and the silane coupling agent, thereby improving the adhesion of the subsequent coating, preventing the coating from falling off and bubbles during use, and at the same time, the metal surface after high-temperature modification is smoother, which is more conducive to the electrophoretic coating to be evenly distributed on the surface.

[0028] In step S4, the coating comprises fine coating and coarse-grained coating, and the fine coating is evenly filled into the elliptical hole structure through an electric field, and the coarse-grained coating is evenly dispersed and deposited on the surface of the metal storage box; wherein the fine coating is configured as a composite structure, including a shell layer and an inner layer, the shell layer is selected from one of phenolic resin and polyethylene, the inner layer is selected from alumina particles and nano-silica, and the coarse-grained coating is selected from zinc powder coating and epoxy resin coating; then the particle size of the alumina particles is 20-40nm, the particle size of the nano-silica is 50-80nm, the particle size of the zinc powder coating is 5-30μm, and the particle size of the epoxy resin coating is 10-30μm.

[0029] It should be noted that since the fine coating is a composite structure with a shell layer and an inner layer, the shell layer will melt and expand during the baking process and combine with the coarse-grained coating deposited on the metal surface; the shell layer material is selected from phenolic resin and polyethylene, both of which will show an expansion effect after reaching a certain temperature.

[0030] As for the preparation of fine coating, the specific preparation process of the shell layer being phenolic resin and the inner layer being aluminum oxide particles is as follows: 10-20 g of phenolic resin is mixed with 100 ml of toluene solvent, and 1-2 g of a cross-linking agent, 0.5-1 g of a rheology modifier and 0.5-1 g of a coupling agent γ-aminopropyltriethoxysilane are added, and the mixture is mixed and stirred until uniform to obtain a composite solution, and then 10-20 g of aluminum oxide particles of the inner layer material are added to the composite solution, and the particle size of the aluminum oxide particles is 20-40 nm, and an ultrasonic treatment device is used for stirring, the ultrasonic power is 100-200 W, and the treatment time is 30-60 min; The coating mixed solution after ultrasonic treatment is spray dried, with a feed temperature of 80-150°C and a discharge temperature of 60-80°C, that is, the coating mixed solution is atomized into tiny droplets through a nozzle, and the solvent is quickly lost in dry air to form a preliminary granular coating. The granular coating after discharge is then subjected to a secondary heat treatment at 100-150°C for 2-4 hours to ensure that the phenolic resin is completely cross-linked and cured, and that the surface of the alumina particles is evenly coated, so that an inner layer and a shell layer structure are formed between the phenolic resin and the alumina particles, forming composite alumina particles, and obtaining a fine coating with a composite structure.

[0031] The electrophoresis solution is made of the following components in percentage by mass: 85-90% water, 0.5-1% disodium hydrogen phosphate, 0.5-1% sodium dihydrogen phosphate, 0.1-0.5% sodium chloride, 0.1-0.5% sodium dodecyl sulfate, 1-2% composite alumina particles, 0.5-1% composite nano-silica, 5-7% zinc powder coating, 3-5% epoxy resin coating, 0.1-0.5% polyethylene glycol, 0.05-0.1% sodium benzoate and 0.1-0.5% ethylene glycol.

[0032] It should be noted that sodium dodecyl sulfate, as a surfactant, reduces the surface tension of the particles, helps the aluminum oxide particles and nano-silica particles to be evenly dispersed in the water and prevent aggregation; polyethylene glycol, as a water-soluble polymer compound, prevents the aggregation of particles through the steric hindrance effect, so that the coating particles remain dispersed in the electrophoretic fluid; and when the fine-grained coating and coarse-grained coating added to the electrophoretic fluid are not dispersed evenly enough, a non-ionic surfactant is appropriately added to the electrophoretic fluid to wet the surface of the coating particles to achieve dispersion, that is, polyoxyethylene fatty alcohol ether is added. This dispersant has little effect on the conductivity of the electrophoretic fluid and will not significantly interfere with the electrophoretic process.

[0033] A direct current electric field is applied to the electrophoretic liquid, the electric field strength is 150-250V, and the electrophoresis time is 2-10min; it should be noted that the fine paint and the coarse-grained paint are added to the electrophoretic liquid and mixed at the same time, and the concentration ratio of each paint added needs to be controlled to the optimal ratio, that is, the fine paint has a sufficient amount to fill the elliptical pore structure, and the coarse-grained paint does not cause blockage; then it is necessary to make the fine paint and the coarse-grained paint in the electrophoretic liquid evenly dispersed, and the paint is fully stirred by adding a dispersant to maintain the uniformity of the paint, and at the same time, a lower electric field strength is used to achieve the fine paint filling the pore structure and prevent the coarse-grained paint from clogging the elliptical pores.

[0034] It should be noted that the electrophoresis method is used to evenly distribute the fine-grained paint and the coarse-grained paint on the metal box. Nano-scale alumina particles and nano-silica particles are small in size and light in weight, and are subjected to relatively small electrophoretic forces in the electric field, move faster, and can be more easily filled into the tiny elliptical pore structure on the metal surface. The fine particles can then make full use of the surface area inside the pores for deposition. In contrast, zinc powder paint and epoxy resin paint have larger particles and slightly heavier weight, are subjected to relatively large electrophoretic forces, move slower, and are mainly deposited on the surface of the metal storage box rather than in tiny pores.

[0035] Among them, since the intensity of the electric field inside the elliptical hole is relatively low, fine particles can use the lower electric field strength to fill the hole. Under the action of the electric field, fine paint is more easily guided into the pore structure for deposition; on the metal surface outside the hole, the electric field strength is relatively high. Under the action of such an electric field, the coarse-grained paint is mainly deposited on the surface of the metal storage box to form a uniform coating, rather than entering the inside of the hole.

[0036] In step S5, when the metal storage box after electrophoretic coating is baked, the temperature is controlled at 100-300°C for 20-40 minutes. During the hot pressing process, the temperature is controlled at 140-200°C, the pressure is 0.5-1.5MPa, and the hot pressing time is 5-10 minutes.

[0037] It should be noted that during the baking process, when the temperature reaches the melting point of the shell material, the shell layer in the fine material structure begins to melt. This process releases the stress inside the coating and enables the coating to flow better and fill the micron-sized elliptical pore structure. As the temperature rises during baking, the shell material expands significantly, allowing the inner layer material to more tightly fill the micron-sized elliptical pores to form a dense protective layer.

[0038] A coating device is designed based on the coating method proposed above, comprising: a coating platform, and an electrolytic cell, a laser drilling system, a modification treatment device and an electrophoresis cell arranged on the coating platform; An anode and a cathode are arranged inside the electrolytic cell. The anode is made of stainless steel, and the cathode is a metal storage box to be treated. It should be noted that a clamp is arranged on the cathode, and the metal storage box is fixed on the clamp. Then the prepared electrolyte is poured into the electrolytic cell to ensure that the liquid level is sufficient to immerse the electrode and the metal storage box to be treated. Turn on the power and adjust the current and voltage to carry out the electrolysis reaction. During the reaction, the generation of bubbles can be observed, that is, the precipitation of oxygen and hydrogen. The electrolysis time is adjusted according to the degree of contamination on the metal surface to ensure that the oil stains and oxide film on the surface of the metal storage box are removed.

[0039] A moving platform is installed on the coating platform, and a laser drilling system is installed on the moving platform, and the laser drilling system includes a nanosecond laser, an optical system and a scanning head arranged in conjunction with the nanosecond laser. It should be noted that before drilling, the structure of the metal storage box is first analyzed and designed to determine the position, aperture size and shape of the holes to be drilled, and the optical system is used to guide the laser beam to the position to be drilled to ensure that all dead corners inside and outside the metal storage box are processed. The scanning head is used to accurately control the position and movement path of the laser beam, and the optical system includes a focusing lens and a reflector to ensure the accuracy of the laser beam.

[0040] Before laser drilling of the metal storage box, the processing path of the elliptical hole structure is planned, and the elliptical hole structure to be processed is designed using CAD software to determine the accurate position and spacing of the holes, and its CAD group is converted into G code that can be recognized by the laser drilling equipment to determine the elliptical hole structure to be processed.

[0041] A laser processing platform is set under the nanosecond laser. This platform is a six-axis linkage platform, which fixes and clamps the metal storage box and realizes multi-directional rotation clamping of the metal storage box, so that the nanosecond laser can process all positions inside and outside the metal storage box; at the same time, segmented drilling is adopted during processing, that is, the metal storage box is repositioned after completing an area, and a monitoring system is equipped in the entire laser processing system to monitor the laser drilling process in real time to ensure precise positioning and processing quality.

[0042] It should be noted that the entire laser drilling process is to fix the metal storage box on the six-axis linkage platform, make sure that no displacement occurs during the processing, align the laser head with the correct position on the metal storage box, pour the converted G code into the nanosecond laser, and perform parameter calibration and focusing. Then, start the laser drilling system and process point by point according to the preset path, that is, the laser head moves along an elliptical trajectory, ablating the metal surface layer by layer until the required depth is reached.

[0043] Among them, during the processing of each elliptical hole, attention should be paid to accurately control the height of the laser focus to ensure the accuracy of the major and minor axis dimensions of the hole. At the same time, after completing the processing of one hole, the laser head moves to the position of the next hole and processes the entire array in turn; after completing the processing, use a three-coordinate measuring machine to check the size of each elliptical hole to ensure the processing accuracy. If deviations are found, adjust the laser parameters or path planning in time to perform supplementary processing.

[0044] The modification treatment equipment includes an impregnation tank, a silane solution tank and a drying equipment; during the modification treatment, the impregnation tank is filled with clean water, the treated metal storage box is placed in the impregnation tank, the metal storage box is impregnated to produce a seamless water film, and immediately immersed in a silane solution tank containing a silane coupling agent solution. After the immersion is completed, the metal storage box is taken out and dried using the drying equipment.

[0045] The electrophoresis tank is filled with electrophoresis liquid, which is prepared according to the formula ratio mentioned in the coating method. The electrophoresis tank is provided with an electrode system and a power supply system. The anode in the electrode system is made of stainless steel, the cathode is a modified metal storage box, and the power supply system is used to apply a DC electric field.

[0046] It should be noted that during the electrophoresis process, in order to further prevent the coarse-grained paint from clogging the elliptical pore structure, a liquid circulation system is also provided in the electrophoresis tank to promote the uniform distribution of the paint particles. The liquid circulation system includes a circulation pump, a filtration system, a flow rate control valve, a flow regulating valve and a PLC control system; wherein, the circulation pump is installed at the bottom of the electrophoresis tank, and the filtration system is configured as a multi-stage filter, which is installed at the inlet and outlet of the circulation pump to remove impurities and incompletely dispersed paint particles in the electrophoresis liquid; an inlet and an outlet are respectively provided at both ends of the electrophoresis tank, and a flow rate control valve is installed at the inlet pipe so that the electrophoresis liquid maintains a uniform flow rate in the entire tank.

[0047] The flow regulating valve is installed at the outlet of the circulation pump to adjust the flow of the electrophoretic liquid, so as to control the migration speed of the paint particles. A liquid level sensor is installed in the electrophoretic tank to keep the liquid level in the tank stable and avoid flow fluctuations. At the same time, a monitoring system is set up. A flow rate sensor is installed at the inlet of the electrophoretic tank to monitor the flow rate of the electrophoretic liquid in real time. A pressure sensor is installed in the circulation loop to monitor the system pressure to prevent excessive pressure from damaging the equipment. A temperature sensor is installed in the electrophoretic tank to monitor the temperature of the electrophoretic liquid, keep the temperature appropriate, and maintain the performance of the paint.

[0048] By setting up a PLC control system that integrates the circulation pump, various valves, sensors and liquid level controller, it can be operated automatically and the pump speed and flow rate can be adjusted in real time to ensure the uniform flow of the electrophoresis liquid.

[0049] A baking oven and a hot press are also provided on the coating platform. The baking oven and the hot press are connected through a conveyor, and a temperature control system is provided inside the baking oven and the hot press. The baking oven bakes the coated metal storage box at high temperature, and the hot press hot presses the surface of the baked metal storage box. When hot pressing the protective layer coated on the inside of the metal storage box, a mold of a specific shape is designed according to the internal structure to apply pressure to the inside of the metal box.

[0050] The hot pressing process is to install the mold that matches the inside of the metal storage box on the hot press, heat the metal storage box to the required heating temperature, put the mold with the metal storage box into the hot press, apply appropriate pressure and maintain it for a period of time, wait for the hot pressing to be completed, and then gradually cool the metal box to stabilize its internal and external shapes. Example

[0051] 1. Test Method (1) Coating adhesion: tested in accordance with GB9286-1998 standard; (2) Salt spray resistance test: Salt spray machine test, refer to GB / T10125, sodium chloride mass concentration: (5±0.5)%, pH value 6.5-7.2, fog drop volume 1-2mL / (h·cm2), nozzle pressure 78.5-137.3kPa (0.8-1.4kgf / cm2); (3) Coating bonding strength test: The coating bonding strength was tested using a MT5305 constant load pre-crack stress corrosion testing machine. The size of the circular tensile specimen was Φ25 mm × 3 mm. The adhesive used was E-7 glue, which was cured at 100 °C for 3 h. The bonding strength was calculated as the arithmetic mean of three parallel specimens.

[0052] 2. Experimental Part 1 1. Preparation of fine coating: (1) A fine coating having a shell layer of phenolic resin (2402 phenolic resin from Dingda (Shandong) New Materials Co., Ltd.) and an inner layer of alumina particles was prepared. The specific preparation process was as follows: 15 g of phenolic resin was mixed with 100 ml of toluene solvent, and 1.5 g of cross-linking agent hexamethylenetetramine, 0.7 g of rheology modifier polyvinyl alcohol (PVA2699 from Xuzhou Hebang Chemical Co., Ltd.) and 0.6 g of coupling agent γ-aminopropyltriethoxysilane were added, and the mixture was mixed and stirred until uniform to obtain a composite solution. Then, 12 g of inner layer material alumina particles with a particle size of 20 nm were added to the composite solution. The alumina particles were stirred using an ultrasonic treatment device with an ultrasonic power of 120 W and a treatment time of 45 min. The coating mixed solution after ultrasonic treatment is spray dried with a feed temperature of 125°C and a discharge temperature of 65°C, i.e. the coating mixed solution is atomized into tiny droplets through a nozzle, which quickly lose the solvent in dry air to form a preliminary granular coating. The granular coating after discharge is then subjected to a secondary heat treatment at 120°C for 3 hours to ensure that the phenolic resin is completely cross-linked and cured, and that the surface of the alumina particles is evenly coated to obtain a fine coating with a composite structure.

[0053] Among them, the prepared fine coating sample was dispersed in anhydrous ethanol and ultrasonically treated for 10 minutes to ensure that the particles were evenly dispersed and not aggregated. A copper mesh (coated with carbon film) was used as a carrier, and a drop of fine coating dispersion was added, and it was allowed to stand until the solvent evaporated completely; Use a high-resolution transmission electron microscope at an acceleration voltage of 200 kV and an observation magnification of 50,000× to 200,000× to observe the overall morphology of the core-shell structure, the core-shell interface, and the internal lattice structure to obtain high-resolution images to determine whether the expected results are achieved (the core is uniformly spherical with a particle size of about 20 nm; the shell is uniformly wrapped with a thickness of about 4-8 nm); 50 particles were randomly selected, their total diameter and core diameter were measured, and the average shell thickness was calculated, resulting in a total diameter of 24-27nm and a shell thickness of 4-7nm. TEM image analysis of the composite structure fine coating with an aluminum oxide particle size of 20nm was performed using a transmission electron microscope, showing that the aluminum oxide particles were the core and the thickness of the coated phenolic resin shell was about 4-7nm.

[0054] According to the above preparation method, a fine coating in which aluminum oxide particles of different particle sizes are wrapped by phenolic resin is prepared, that is, a composite structure fine coating in which the particle sizes of aluminum oxide particles are 30nm and 40nm respectively is obtained. It should be noted that a layer of phenolic resin is wrapped on the outer surface of the aluminum oxide particles. Although the particle size range is slightly increased, its particle size is still within the nanometer range.

[0055] (2) Prepare a composite structure fine coating with a shell layer of polyethylene (LDPE 2426H from Suzhou Wenge Plastics Co., Ltd.) and an inner layer of aluminum oxide particles. The specific preparation process is as follows: 15 g of polyethylene is mixed with 100 ml of trichloroethylene solvent, and 0.7 g of rheology modifier polymethyl methacrylate (PMMA MF501 from Shanghai Honglei Plastics Co., Ltd.) and 0.6 g of coupling agent γ-aminopropyl triethoxysilane are added. The mixture is mixed and stirred at a high temperature of 120°C until uniform to obtain a composite solution, which is then cooled to 80°C. 12 g of aluminum oxide particles as the inner layer material are added to the composite solution, and the particle size of the aluminum oxide particles is 20 nm. The mixture is stirred using an ultrasonic treatment device with an ultrasonic power of 120 W and a treatment time of 45 min. The coating mixed solution after ultrasonic treatment is spray dried with a feed temperature of 80°C and a discharge temperature of 60°C, i.e. the coating mixed solution is atomized into tiny droplets through a nozzle, which quickly lose the solvent in dry air to form a preliminary granular coating. The granular coating after discharge is then subjected to a secondary heat treatment at 120°C for 3 hours to ensure that the surface of the alumina particles is evenly coated to obtain a fine coating with a composite structure.

[0056] According to the above preparation method, a fine coating in which aluminum oxide particles of different particle sizes are wrapped by polyethylene is prepared, that is, a composite structure fine coating in which the particle sizes of aluminum oxide particles are 30nm and 40nm respectively is obtained. It should be noted that a layer of polyethylene is wrapped on the outer surface of the aluminum oxide particles. Although the particle size range is slightly increased, its particle size is still within the nanometer range.

[0057] (3) For a composite structure fine coating with an inner layer of nano-silica and a shell layer of phenolic resin or polyethylene, several fine coatings were prepared according to the above two preparation methods, namely, a composite structure fine coating with an inner layer of nano-silica and a nano-silica particle size of 55nm, 65nm, and 75nm respectively. Example

[0058] Since laser drilling is performed on the surface of the metal storage box, the elliptical hole structures of different sizes affect the adhesion of coatings with different particle sizes, and the different shell materials of fine particle sizes also affect the coating effect of the metal storage box, the rust-proof performance of the metal storage box finally obtained will be different. Therefore, the size of the elliptical hole structure is prepared according to the following embodiment to obtain a metal storage box coated with a protective layer for testing: Example 1

[0059] Select a number of metal storage boxes made of the required manganese alloy, perform surface treatment on the metal storage boxes, remove oil stains and oxide films on the surface of the metal storage boxes by electrolysis, that is, use clean water to preliminarily clean the metal storage boxes to remove most of the impurities and oil stains on the surface, install a stainless steel anode on one side of the electrolytic cell, fix the metal storage box to be treated on the cathode fixture, pour the prepared electrolyte into the electrolytic cell, and ensure that the liquid level immerses the electrode and the metal storage box; Connect the electrodes to the power supply, connect the stainless steel anode to the positive pole, and the metal storage box cathode to the negative pole. Turn on the power supply and adjust the current density to 0.3A / d㎡, and the voltage to 8V. Start the electrolysis reaction for 12 minutes. Wait for the electrolysis to end, and use clean water to fully clean the metal storage box to remove the electrolyte residue, and neutralize it. Then put the metal storage box in a drying box and dry it at low temperature. The raw materials for preparing the electrolyte include 15% sulfuric acid, 10% phosphoric acid and 75% water solvent by mass percentage. During the preparation process, sulfuric acid is slowly added to the water solvent while stirring to avoid excessive temperature. After the sulfuric acid is completely dissolved, phosphoric acid is slowly added and stirring is continued until completely mixed to obtain the electrolyte. The surface of the metal storage box that has been treated by surface drilling is processed by laser. The laser moves along the path of the ellipse, repeatedly scans and etches, and finally forms an elliptical shape, processing a number of micron-level elliptical hole structures. The nanosecond laser processing system is used for laser drilling of the surface of the metal storage box. The parameters of the nanosecond laser processing system are set as follows: speed of 50 mm / s, frequency of 15 kHz, power of 15 W, and a micron-level elliptical hole structure is processed, with a short axis of 10 μm, a long axis of 30 μm, and a depth of 30 μm. The laser-processed metal storage box was soaked with clean water to produce a seamless water film, and then immediately immersed in a 1% γ-aminopropyltriethoxysilane solution for 10 minutes. After the immersion, the metal storage box was taken out and dried at a high temperature of 100°C for 25 minutes. Prepare an electrophoresis tank, add electrophoresis liquid, immerse a metal storage box as a cathode into the electrophoresis liquid, apply a direct current electric field to evenly disperse the fine paint and the coarse-grained paint in the electrophoresis liquid on the surface of the metal storage box and in the elliptical hole structure to form a layered structure; wherein the two kinds of paints of the fine paint and the two kinds of paints of the coarse-grained paint are directly added to the electrophoresis liquid, and the current electric field strength is 160V, the electrophoresis time is 8min, and the electrophoresis liquid is made of the following components in mass percentage: 86% water, 0.6% disodium hydrogen phosphate, 0.5% sodium dihydrogen phosphate, 0.3% sodium chloride, 0.3% sodium dodecyl sulfate, 1.5% composite alumina particles, 0.6% composite nano-silica, 6% zinc powder paint, 4% epoxy resin paint, 0.3% polyethylene glycol, 0.07% sodium benzoate, 0.3% ethylene glycol, and 0.5% polyoxyethylene fatty alcohol ether; There are two kinds of fine coatings. The first kind of coating is composite alumina particles, the shell layer of which is phenolic resin and the inner layer is alumina particles. The second kind of coating is composite nano-silica, the shell layer of which is phenolic resin and the inner layer is nano-silica. The particle size of alumina particles is 20nm, the particle size of nano-silica is 55nm, the particle size of zinc powder coating is 5μm (Zn-420A from Shanghai Jinyuan Zinc Powder Co., Ltd.), and the particle size of epoxy resin coating is 10μm (EP-828 from Jiangsu Sanmu Group Co., Ltd.). The dip-coated metal storage box is baked at high temperature. During the baking process, the shell layer will melt and expand, combining with the coarse-grained coating deposited on the metal surface. The baking temperature is 220°C and the time is 25 minutes. It is hot-pressed to form a uniform protective coating. During the hot-pressing process, the temperature is controlled at 180°C, the pressure is 1.0MPa, and the hot-pressing time is 6 minutes. Example 2

[0060] The preparation steps are generally the same as those in Example 1. The laser moves along an elliptical path, repeatedly scans and etches, and finally forms an elliptical shape, processing a number of micron-level elliptical hole structures. The difference is that when laser drilling the metal storage box, the parameters of the nanosecond laser processing system are set to: speed of 100 mm / s, frequency of 25 kHz, power of 20 W, and a micron-level elliptical hole structure is processed, with a short axis of 20 μm, a long axis of 60 μm, and a depth of 50 μm. After a series of subsequent processing, a metal storage box coated with a protective layer is obtained. Example 3

[0061] The preparation steps are generally the same as those in Example 1. The laser moves along an elliptical path, repeatedly scans and etches, and finally forms an elliptical shape, processing a number of micron-level elliptical hole structures. The difference is that when laser drilling the metal storage box, the parameters of the nanosecond laser processing system are set to: speed of 150 mm / s, frequency of 30 kHz, power of 25 W, and a micron-level elliptical hole structure is processed, with a short axis of 30 μm, a long axis of 90 μm, and a depth of 70 μm. After a series of subsequent processing, a metal storage box coated with a protective layer is obtained. Example 4

[0062] The preparation steps are generally the same as those in Example 1, except that, when the metal storage box is laser punched, the position of the laser beam is fixed to perform drilling, and finally a circular hole shape is formed, and several micron-level circular hole structures are processed. The parameters of the nanosecond laser processing system are set to: speed of 150 mm / s, frequency of 25 kHz, and power of 35 W, and a micron-level circular hole structure with a diameter of 20 μm and a depth of 50 μm is processed. After a series of subsequent processing, a metal storage box coated with a protective layer is obtained.

[0063] For the elliptical hole structures and circular hole structures with different pore sizes and depths obtained in Examples 1-4, and the surface of the metal storage box is coated with fine-grained paint and coarse-grained paint, the following is a performance test of the coating obtained by coating the composite structure in which the shell layer of the fine paint is phenolic resin, as shown in Table 1: Table 1

[0064] It can be seen from the data in the table that elliptical hole structures with different aperture sizes are processed by laser, and fine coatings and coarse-grained coatings with different particle sizes are used to carry out coating tests on the surface of the metal box to obtain the results. According to the comparison of the results obtained in Example 1, it can be found that the particle size of the fine coating is completely smaller than the elliptical hole and can be fully filled into the elliptical hole. However, the zinc powder coating in the coarse-grained coating is tested with particle sizes of 5μm, 15μm and 25μm. When the particle size is smaller than the elliptical hole, part of the zinc powder coating will enter the elliptical hole structure during electrophoretic coating, hindering the entry of the fine coating, resulting in the formation of an uneven coating in the hole, that is, the fine coating cannot evenly cover the inner surface of the hole, resulting in uneven coating thickness, resulting in reduced adhesion. At this time, the adhesion of the coating is the lowest and the bonding strength is also low.

[0065] At the same time, during the final baking and hot pressing, the shell layer will melt and produce a certain expansion effect, so that a dense coating is formed in the elliptical hole structure. However, when the coarse-grained paint is also filled into the elliptical hole, even if the melting and expansion of the shell layer make the coatings more tightly connected, pores will still appear between the coatings. This is because the size and shape of the added paint particles are uneven, and the changes in temperature and pressure cause the coarse-grained paint to move slightly and extrude, forming pores at the interface, resulting in reduced adhesion of the coating, which in turn affects the anti-rust performance of the coating.

[0066] It can also be seen from the data in the above table that the results of using fine-grained paint and coarse-grained paint of the same type of particle size to coat the elliptical hole structure with different apertures on the metal box surface are compared. When the coarse-grained paint with a particle size larger than the elliptical hole is used for coating, the coarse-grained paint will not enter the inside of the elliptical hole, but will form a uniform covering layer outside the hole, ensuring that the inside and outside of the hole can be completely coated, and the hole will not be blocked by the coarse-grained paint and affect the uniformity of the coating. At the same time, it ensures that the fine paint can form a closer bond with the surface of the substrate, thereby improving the durability of the coating; while using electric field coating in the electrophoretic liquid Although the liquid circulation system is used to circulate the paint to prevent clogging, when the particle size of the coarse-grained paint is approximately equal to the minor axis size of the elliptical hole, the flow circulation cannot completely prevent clogging, which leads to insufficient filling of the fine paint, making the coating uneven, and further affecting the coating adhesion and coating effect; from the data in the table, it can be seen that when 40nm alumina particles and 75nm nano-silica are used, and the coarse-grained paint uses 25μm zinc powder paint and 30μm epoxy resin paint, and the minor axis of the filled elliptical hole structure is 20μm, the coating effect is the highest.

[0067] By comparing Example 4 with other examples, it can be learned that the adhesion performance of the coating obtained by filling the circular hole structure with fine paint is poor. This is because the surface interface within the circular hole structure is semi-circular, which is more curved than the arc of the elliptical hole structure, so that the fine paint at the edge cannot be completely filled into the circular groove, resulting in pores, while the nearly smooth surface of the elliptical hole structure provides more interfaces for the paint to adhere and fill; therefore, after the circular groove structure is filled with paint, after baking and hot pressing, the problem of uneven paint distribution is more likely to occur.

[0068] It can be explained that the performance of the metal storage box coating obtained by using the coating filled with the elliptical hole structure is more stable and has better corrosion resistance than the metal storage box coating obtained by using the coating filled with the circular hole structure. The reason is that the aluminum oxide particles and nano-silica in the fine coating are filled in the elliptical hole structure. After baking, the fine coating with a shell layer of polyester resin material expands and combines with the zinc powder coating and epoxy resin coating deposited on the metal surface, thereby realizing the layered structure of the coating and improving the mechanical interlocking between the coating and the metal surface at the edge of the elliptical hole groove, thereby enhancing the adhesion of the coating. The reason for the mechanical interlocking is that the edge of the elliptical groove is sharper than that of the circular groove, thereby increasing the local contact area of ​​the edge, thereby providing more contact points after the coating is cured, thereby enhancing the mechanical interlocking between the coating and the metal surface, and the major axis and minor axis of the elliptical groove exhibit different stress concentration effects under stress, which prompts the coating material to form a tighter bond at the edge of the groove, further improving the adhesion of the coating.

[0069] 3. Experimental Part 2 According to Experimental Part 1, the optimal particle size of fine-grained paint and coarse-grained paint and the elliptical pore structure with the optimal pore size can be obtained. The coating effect obtained by combining the two is the best. Since the shell material of the fine-grained paint will also affect the coating effect, the anti-rust performance of the metal storage box obtained in the end will be different. The following experiments are conducted: Example 2-1 Under the preparation conditions of Example 2, 40nm alumina particles and 75nm nano-silica are used, 25μm zinc powder paint and 30μm epoxy resin paint are used as coarse-grained coatings, and phenolic resin is selected as the shell material in the fine coating. The metal storage box is coated with the above materials, and then a series of subsequent processing is carried out to obtain a metal storage box coated with a protective layer.

[0070] Comparative Example 1 The preparation method is the same as that of Example 2-1, except that a fine coating whose shell material is polyethylene is used for coating, and then a series of subsequent processing is performed to obtain a metal storage box coated with a protective layer.

[0071] According to the characteristics of phenolic resin and polyethylene, the baking temperature and hot pressing conditions were adjusted, the coating was baked and hot pressed, and then the coating performance was tested, and the following results were obtained, as shown in Table 2: Table 2

[0072] It can be seen from the above table that due to the different characteristics of the shell material, the use of different baking temperatures will also have a certain impact on the performance of the coating. When the baking temperature becomes higher and higher, the adhesion performance of the coating suddenly decreases. Due to the higher temperature, the epoxy resin and the phenolic resin of the shell material are partially thermally degraded, which weakens the mechanical properties and makes the coating more brittle, resulting in insufficient adhesion of the coating.

[0073] Comparing the coating obtained by baking at 260°C for 20 min when the shell material is phenolic resin, and the coating obtained by baking at 120°C for 20 min when the shell material is polyethylene, the adhesion of the two coatings is excellent. However, by comparing the salt spray resistance and the bonding strength, it can be seen that the fine coating using the shell material of phenolic resin has better corrosion resistance and a better adhesion. This is because the fine coating using the shell material of phenolic resin melts during baking and produces a relatively stable expansion effect, so that the inner layer of alumina particles and nano-silica are completely filled in the elliptical hole structure, especially the edges of the elliptical holes are also filled.

[0074] At the same time, after the expansion effect is produced, the shell material phenolic resin has a larger contact area with the coarse-grained coating deposited on the metal surface and combines, making the coating performance more stable, that is, the phenolic resin produces an expansion effect at high temperature, flows and fills the gaps between the zinc powder particles, and enhances the adhesion through mechanical interlocking. At the same time, the phenolic resin softens and expands at high temperature, flows and fills the irregular structure on the surface of the epoxy resin, and forms a strong bond through mechanical interlocking; and when polyethylene produces an expansion effect at high temperature, it will combine with the zinc powder coating and the epoxy resin coating to form a certain degree of mechanical interlocking, but the expansion effect of polyethylene is unstable, and the alumina particles and nano-silica in the filling elliptical hole structure cannot effectively form a strong bond with the alumina particles and nano-silica, which also causes the positions of the alumina particles and nano-silica to change, causing the compactness of the coating structure to decrease, thereby affecting the performance stability of the coating.

[0075] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for coating a durable rust-proof metal storage box with a protective coating, characterized in that: The following steps are involved: S1. Place the required metal storage box into an electrolytic bath, and remove the oil and oxide film on the surface of the metal storage box by electrolysis; S2, performing laser drilling on the surface of the treated metal storage box to produce a number of micron-level elliptical hole structures; S3, placing the metal storage box obtained in S2 into a silane coupling agent solution and performing high-temperature modification; S4, pouring electrophoresis liquid into the electrophoresis tank, immersing the metal storage box as a cathode into the electrophoresis liquid, applying a DC electric field to evenly disperse the coating in the electrophoresis liquid onto the surface of the metal storage box and into the elliptical hole structure to form a layered structure; The coating comprises fine coating and coarse-grained coating, and the fine coating is uniformly filled into the micron-scale elliptical pore structure through an electric field, and the coarse-grained coating is uniformly dispersed and deposited on the surface of the metal storage box; wherein the fine coating is set as a composite structure, including a shell layer and an inner layer, the shell layer is selected from one of phenolic resin and polyethylene, the inner layer is selected from aluminum oxide particles with a particle size of 20-40nm and nano-silica with a particle size of 50-80nm, and the coarse-grained coating is selected from zinc powder coating with a particle size of 5-30μm and epoxy resin coating with a particle size of 10-30μm; The micron-scale elliptical hole structure has a short axis of 10-30 μm, a long axis of 30-90 μm, and a depth of 30-70 μm; S5. The metal storage box obtained in S4 is baked at high temperature and hot-pressed to form a uniform protective coating.

2. A method for coating a durable rust-proof metal storage box with a protective coating according to claim 1, characterized in that: The metal storage box in S1 is made of iron alloy, manganese alloy or chromium alloy.

3. The method for coating a durable rust-proof metal storage box with a protective coating according to claim 1, characterized in that: A nanosecond laser processing system is used for laser drilling on the surface of the metal storage box, and the parameters of the nanosecond laser processing system are set as follows: speed of 10-300 mm / s, frequency of 10-30 kHz, and power of 5-50 W.

4. The method for coating a durable rust-proof metal storage box with a protective coating according to claim 1, characterized in that: The silane coupling agent in S3 is a 1% γ-aminopropyltriethoxysilane solution; wherein, the high-temperature modification process is: soaking the metal storage box with clean water to produce a seamless water film, and immediately immersing it in the γ-aminopropyltriethoxysilane solution for 8-12 minutes. After the immersion is completed, take out the metal storage box for drying, and keep it at a high temperature of 100-130°C for 20-30 minutes.

5. The method for coating a durable rust-proof metal storage box with a protective coating according to claim 1, characterized in that: The electrophoresis liquid in S4 is made of the following components in mass percentage: water 85-90%, disodium hydrogen phosphate 0.5-1%, sodium dihydrogen phosphate 0.5-1%, sodium chloride 0.1-0.5%, sodium dodecyl sulfate 0.1-0.5%, composite alumina particles 1-2%, composite nano-silica 0.5-1%, zinc powder coating 5-7%, epoxy resin coating 3-5%, polyethylene glycol 0.1-0.5%, sodium benzoate 0.05-0.1%, ethylene glycol 0.1-0.5%; The fine coating is a mixture of two coatings. The first coating is composite alumina particles, the shell of which is phenolic resin and the inner layer is alumina particles. The second coating is composite nano-silica, the shell of which is phenolic resin and the inner layer is nano-silica.

6. The method for coating a durable rust-proof metal storage box with a protective coating according to claim 1, characterized in that: In S4, a direct current electric field is applied to the electrophoresis liquid, the electric field strength is 150-250V, and the electrophoresis time is 2-10min.

7. A coating device for a durable rust-proof metal storage box coated with a protective coating, based on a coating method for a durable rust-proof metal storage box coated with a protective coating according to any one of claims 1 to 6, characterized in that: include: A coating platform, and an electrolytic cell, a laser drilling system, a modification treatment device and an electrophoresis tank arranged on the coating platform; An anode and a cathode are arranged inside the electrolytic cell, the anode is made of stainless steel, and the cathode is a metal storage box to be processed; a mobile platform is installed on the coating platform, and the laser drilling system is installed on the mobile platform, and the laser drilling system includes a nanosecond laser, an optical system and a scanning head arranged in cooperation with the nanosecond laser; The modification treatment equipment includes an infiltration tank, a silane solution tank and a drying device; the electrophoresis tank is filled with electrophoresis liquid, and an electrode system and a power supply system are arranged in the electrophoresis tank, the anode in the electrode system is made of stainless steel, the cathode is a modified metal storage box, and the power supply system is used to apply a DC electric field.

8. The coating device for a durable rust-proof metal storage box coated with a protective coating according to claim 7, characterized in that: The coating platform is also provided with a baking oven and a hot press, the baking oven and the hot press are connected through a conveyor, and a temperature control system is provided in the baking oven and the hot press.

Citation Information

Patent Citations

  • Method for planting solid lubricating material in laser micropore template

    CN107190304A

  • Molybdenum disulfide and polytetrafluoroethylene solid lubricant injected into friction surface and micropore array wear-resistant coating

    CN110747461A

  • Preparation method of oxide film on surface of aluminum alloy formwork

    CN111074321A

  • Electrophoretic coating process for vehicle frame

    CN111235620A

  • Nodular cast iron pipe fitting coating structure and preparation method thereof

    CN114438571A

Cited By

  • Electroplating device and electroplating process for diamond saw wire

    CN121023616A